Pengaruh Suhu Pemanasan dan Lama Pemanasan Terhadap Kadar Vitamin C dalam Buah Melon - Icha R (Herbal Medicine Journal, 2021)
Fruits are a type of food that contains nutrients, vitamins and minerals which are generally very good for consumption every day. Vitamin C is one of the vitamins contained in fruits. The loss of vitamin C in fruit processing depends on the type and process used, as well as the water-soluble vitamins. The purpose of this study was to determine the effect of heating temperature and heating time on the vitamin C content in melon juice. The method used in this research is using the ultraviolet spectrophotometric method. Green melon juice was treated with heating temperature and heating time with variations in heating temperature (30 ° C, 60 ° C, and 90 ° C) and variations in heating time (15 minutes, 30 minutes, and 45 minutes). The results showed that the orange melon juice and green melon juice by heating decreased the Vitamin C content. Heating of fruit juices often occurs during the sterilization process, so if the vitamin content in the material is to be maintained, sterilization must be carried out in a very short time. Heating temperature and heating time have a significant effect on the content of vitamin C in green and orange melon juice.